O Programa institucional de bolsa de iniciação à docência – PIBID e seus impactos sobre a formação inicial de professores - Siqueira, Cesar Wagner Gonçalves (2017)
The present work, entitled The Teaching Initiation Institutional Program (PIBID) and its impacts on initial teacher education, had as its general objective to understand how the formative experience of PIBID / UECE has improved the teaching knowledge learned by scholarship students are enrolled in the CECITEC degree courses. Specifically: to reflect on the limits and possibilities of PIBID regarding the training of future teachers and on the contribution of articulation theory and practice in this process; to analyze how the activities proposed by PIBID contribute to the learning of the teaching knowledge; to analyze, through the Program, how the fellows understand the professional teaching performance in the context of the classroom. The study had as theoretical contribution: the teaching knowledge and the learning of teaching. The research was based on the qualitative approach. In this research participated as subjects forty-nine undergraduate students, three university professors and eight basic education teachers, scholars of the Program. The procedures used to collect data were: interview through a questionnaire, with closed and open questions. In addition to this procedure, we used document analysis. The study assumes that the Program has made possible the improvement in the initial training of the scholarship holders. The results show that the actions undergone in the Program enabled the scholars to have varied perceptions about the work of the teachers, where the reflexive exercise was based on the reality of the school and the teachers' practice. Initially, we identified the profile of the undergraduate students from the studied context and their impressions about the Program. The context in which the actions of the PIBID are carried out gave the scholars a better understanding of the theory and practice articulation in the formative process. It was identified the development of four didactic-pedagogical strategies: insertion of the undergraduate students in the classroom; planning of activities for intervention; construction of materials and didactic-pedagogical strategies to be applied in classroom practice; and study groups. It was verified that the undergraduate students constructed pedagogical, disciplinary, curricular knowledge and experiences through the actions of the Program. The experience of participating in PIBID enabled the scholars to understand what it is to be a teacher, the difficulties and complexity of the work and what knowledge they need to mobilize to take on a classroom, contributing to build the teaching identity. Therefore, we conclude that the subprojects of PIBID / CECITEC provided their scholars with meaningful learning about teaching work, effectively contributing to a better articulation between theory and practice, constituting a strong advance in the policy aimed to initial teachers training.